DOES FINANCIAL DISTRESS HAS AN EFFECTS ON AUDIT REPORT LAG? (STUDY ON MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE) - Nur Khamisah; Anisa Listya; Nyimas Dewi Murnila Saputri (AKUNTABILITAS, 2021)
This study aims to examine the effect of financial distress on audit report lag and how the size of CPA Firm moderate the effect between financial distress and audit report lag. This study was held at manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The final sample there were 318 observations, with a purposive sampling method. The variable financial distress is measured by the Altman Z Score proxy, which is the best model for measuring the state of financial distress being experienced by the company. The size of CPA Firm is measured by dummy variables, given a value of 1 if it is a Big Four CPA Firm and 0 if it is not a Big Four CPA Firm. This study use multiple linear regression to analyze the data. Based on the results of the analysis found that financial distress has negative and significant effect on audit report lag. It means that the smaller the Z Score of a company (which means the company is experiencing financial distress), the longer the financial statement audit process will be. This negative relationship between financial distress is strengthened by the size of CPA Firm.